Characterisation and Material Removal Properties of the RAP™ Process - O'Brien, William John (Cranfield University, 2011)
The Reactive Atom Plasma® (RAP) process is a plasma chemical etching process. RAP was developed at RAPT Industries as a process for removing subsurface damage from silicon carbide optics. The process is being investigated at Cranfield University as a novel method for the fine surface correction of large optics, with the aim of shortening the manufacturing period of the next generation of large telescopes. RAP offers material removal rates that are up to 10 times higher than those of ion beam figuring, the current state-of-the-art technique and the convenience in that it can be operated at atmospheric pressure. Cont/d.